Protein expression of STRO-1 cells in response to different topographic features - Fahsai Kantawong (2018)
Human skeletal stemcells (STRO-1 positive) display distinct responses to different topographical features. On a flat surface, skeletal cells spread, and in vitro, they typically display a polarized, fibroblast-like morphology. However, on microgrooved surfaces, these cells prefer to stretch along the grooves forming a similar morphology to in vivo, bipolarized fibroblasts. In contrast, on nanopits, these cells display a polygonal and osteoblastic phenotype. We have examined mechanotransduction events of STRO-1 positive in response to fibroblastic, microgrooved and osteogenic, controlled disorder nanopit, topographies using proteomics after 3 days in culture. Protein expression profiles were analyzed by difference gel electrophoresis to identify proteins that showed modulation of expression in response to different topographic features to assess early decision events in these cells on these discrete topographies. After only 72 hours in culture, STRO-1 positive displayed differential regulations of families of proteins involved in cell migration and proliferation. The current study indicated that osteogenic decision specific events had already occurred. Runx2 was localized in nuclei of the skeletal stem cells on the osteogenic nanopits; however, few signaling pathway changes were observed. This study demonstrated that micro- and nanotopographies activated skeletal stem cells at different times and with distinct mechanotransduction profiles. © 2011 Fahsai Kantawong et al.